Preventing bullying in schools: a social and emotional approach to early intervention - Bradshaw, Catherine P (The Norton series on social emotional learning solutions, 2019)
Bullying : it isn't just child's play -- Understanding bullying -- How does bullying impact student, teachers, and schools? -- Preventing bullying in the classroom -- What can we do to prevent bullying before it happens?